Realizing reliability in forensic science from the ground up - Gabel, Jessica D. (--Illinios: Northwestern University, 2014)
This articles emphasizes that forensic flaws persist and that deficiencies in forensic science have harrowing implications for criminal justice. In the wake of numerous calls for forensic reform, I propose that we use existing models and frameworks already in place to improve the quality and cost of the U.S. forensic science program, rather than creating an entirely new and unaffordable system. At bottom, this article calls for collaboration between labs, universities and research centers, and the criminal justice system with the goal of making forensic science more reliable.
Keywords: Criminal law